TRANSFORMASI ILMU KALAM: TELAAH PEMIKIRAN FAZLUR RAHMAN DAN MUHAMMAD IQBAL DALAM PENDIDIKAN ISLAM MODERN - Imam Aris Utomo; Sri Wahyuni; Khoirun Nisa Mutmainah; Zahra Naila Abhista; An Nisaa Nur Sifa Az Zahra (EDUCATIONAL : Jurnal Inovasi Pendidikan & Pengajaran, 2026)
ABSTRACT Shifting social landscapes, rapid advances in digital technology, and the changing nature of religious authority have intensified the need to reconstruct Islamic theology (ilm al-kalam) in ways that respond to the challenges faced by contemporary Muslim societies. This article explores the synthesis of Fazlur Rahman's and Muhammad Iqbal's thought to examine their contributions to the development of modern ilm al-kalam, particularly in relation to Islamic education, religious rationality, and the integration of knowledge. The study employed a qualitative library research approach by examining 31 scholarly publications published within the last five years, selected based on thematic relevance and academic quality. The data were analyzed using a descriptive-interpretative approach through thematic synthesis to identify patterns of thought, conceptual relationships, and their relevance to contemporary contexts. The findings indicate that the reconstruction of modern ilm al-kalam extends beyond theological reinterpretation by integrating rationality, contextuality, ijtihad, and khudi as the foundations for renewing Islamic education. The synthesis of the neo-modernism paradigm, double movement, ijtihad, and khudi produces a conceptual framework that strengthens the development of an integrative, moderate, and adaptive model of Islamic education in the digital era. These findings highlight that the reconstruction of modern ilm al-kalam provides an important epistemological foundation for strengthening religious moderation, digital literacy, and the development of learners who are critical, reflective, and responsive to social change. ABSTRAK Perubahan lanskap sosial, kemajuan teknologi digital, dan bergesernya otoritas keagamaan menghadirkan kebutuhan akan rekonstruksi ilmu kalam yang mampu menjawab tantangan masyarakat Muslim kontemporer. Artikel ini mengeksplorasi sintesis pemikiran Fazlur Rahman dan Muhammad Iqbal untuk menjelaskan kontribusinya terhadap pengembangan ilmu kalam modern dalam perspektif pendidikan Islam, rasionalitas keagamaan, dan integrasi ilmu pengetahuan. Kajian disusun melalui pendekatan kualitatif berbasis library research dengan menelaah 31 literatur ilmiah terbitan lima tahun terakhir yang dipilih berdasarkan relevansi tema dan kualitas akademik. Data dianalisis secara deskriptif-interpretatif melalui sintesis tematik untuk mengidentifikasi pola pemikiran, keterkaitan konsep, dan relevansinya terhadap konteks kontemporer. Kajian ini menunjukkan bahwa pembaruan ilmu kalam tidak hanya bertumpu pada reinterpretasi teologi, tetapi juga pada integrasi rasionalitas, kontekstualitas, ijtihad, dan kesadaran diri sebagai landasan pembaruan pendidikan Islam. Sintesis paradigma neo-modernism, double movement, ijtihad, dan khudi menghasilkan kerangka konseptual yang memperkuat pengembangan pendidikan Islam yang integratif, moderat, dan adaptif terhadap transformasi digital. Temuan tersebut menegaskan bahwa rekonstruksi ilmu kalam modern memiliki makna strategis sebagai fondasi epistemologis untuk memperkuat moderasi beragama, literasi digital, serta pembentukan peserta didik yang kritis, reflektif, dan responsif terhadap perubahan sosial.